Validation in Reading Comprehension. (October 2013) - Singer, Murray
Language comprehension involves analysis at the level of the word, sentence, and message and the integration of message meaning with the prior discourse and world knowledge. Contemporary research converges on another facet of comprehension: the validation of message consistency. Existing evidence already favors several principles in validation of reading and listening. Validation is initiated immediately and is routine rather than requiring intentional strategies. Successful validation is a precondition to updating the situational representation of the message. Validation applies to discourse inferences as well as explicit assertions. Finally, the memory-retrieval processes that enable validation closely resemble those of intentional discourse memory. Competing observations of people's validation failures are proposed to systematically stem from features of the message, understander, and comprehension task. Therefore, theoretical analysis that accommodates both successful and deficient language validation ought to be attainable.